1992
DOI: 10.1111/j.1151-2916.1992.tb05497.x
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Texture and Grain Growth in a Supperplastic SiAlON

Abstract: A fine-grained superplastic p'-silicon nitride solid solution (SiAION) was found to develop elongated grains and a pronounced texture during tensile deformation at 1550°C. The texture development is well-described by a geometrical model of grain rotation in accordance with the strain field. Once aligned, grains can then grow with little constraint due to impingement and often coalesce into each other. With the above microstructural development, the stressstrain curve displayed unusually strong strain hardening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 16 publications
6
60
0
Order By: Relevance
“…In the case of tensile stress, the c-axis oriented texture preferentially develops. Wu and Chen [112] reported that the large tensile strains at 1550 • C allow hot-pressed β-Sialon with a fine-grained microstructure at 1550 • C to develop elongated grains and a very strong c-axis oriented texture. The degree of orientation increases with increased tensile strain.…”
Section: Hot-forgingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tensile stress, the c-axis oriented texture preferentially develops. Wu and Chen [112] reported that the large tensile strains at 1550 • C allow hot-pressed β-Sialon with a fine-grained microstructure at 1550 • C to develop elongated grains and a very strong c-axis oriented texture. The degree of orientation increases with increased tensile strain.…”
Section: Hot-forgingmentioning
confidence: 99%
“…Assuming a rodlike morphology for β-Si 3 N 4 grains and the absence of any interaction between neighboring grains, grain rotation models have been developed to describe the texture development in Si 3 N 4 ceramics by Wu and Chen [112] and Lee and Bowman [111]. For grain rotation under tension, Wu and Chen obtained the following equation Lee and Bowman described grain rotation under compression as follows.…”
Section: Grain Rotation Modelmentioning
confidence: 99%
“…A, n and p in this equation are constants [2][3][4]8,11,13,17,27,28]. According to the above-mentioned creep equation, the applied stress, the grain size of the deformed material, and the temperature affect the strain rate; namely, a fine grain is favorable for plastic deformation at a high strain rate under constant stress and temperature conditions.…”
Section: Preparation Of Fine Powdermentioning
confidence: 99%
“…These powders in some cases were used without grinding. For processes involving grinding, a process known as attrition milling was employed; however, the results of grinding, e.g., particle size or particle size distribution, were not reported [2,[4][5][6]12,13]. Another process employed for grinding is known as mechanochemical grinding [18].…”
Section: Commercial Fine Powdersmentioning
confidence: 99%
“…Furthermore, these authors showed that a number of ceramic oxide exhibit the same trend, regardless of the test temperatures and strain rates employed. Figure 2 represents the data of various kinds of ceramics, such as ceramic oxides (Y-TZP [1], Hydroxyapatite [5], PbTiO~ [7], Mn-Y-TZP [10], Y-TZP/20-80 wt.% A1203 composites [2,14], Mg-AI203 [17], fl-SiAION [19], 12Ce-CZP [211, 2Y-TZP [21], fl-Spodumene glass [22]), ceramics with covalent bonding (SiC/Si3N4 composite [13], A1203-Y203-SiC/Si3N4 composite [20]) and carbides (Fe3C/20Fe composite [8] and Fe~AICoJ10FeA1 composite [34]). The data points of 3Y-TZP and 3Y-TZP and 3Y-TZP/A1203 composites are not explicitly shown in this figure as they were shown previously in the reference [24].…”
Section: Tensile Elongation Behavior Of Superplastic Metallic Alloys mentioning
confidence: 99%